Implementasi Program Keluarga Harapan (PKH) Pada Desa Sungai Kakap Kabupaten Kubu Raya - Agus Eko Tejo Sasongko; Era Prestoroika; Debbie Yuari Siallagan (Universitas Muhammadiyah Mataram, 2021)
Poverty is considered as one of the major problems faced by the Indonesian people which has a direct impact on the community in fulfilling their basic needs. This problem obviously has an impact on the social welfare of the community. For this reason, the community needs assistance to fulfill basic needs which include food, health amenities and education. One of the efforts made by the government to overcome the problem of poverty and improve community welfare is the Family Hope Program. This program is the provision of conditional social assistance to poor families. It is in accordance with the Regulation of the Minister of Social Affairs Number 1 of 2018 concerning the Family Hope Program. With the implementation of this program in Sungai Kakap Village, Kubu Raya Regency, it is hoped that it can help people who are unable to meet the needs of life, especially education and health, for families classified as Very Poor Households. The purpose of this study was to determine the implementation of the Family Hope Program (PKH) in Sungai Kakap Village, Kubu Raya Regency. This study used descriptive qualitative method. Data collection techniques employed are interviews, observation and documentation studies. The research findings show that the recipients of the Family Hope Program in Sungai Kakap Village, Kubu Raya Regency, increased from 2019 to 2020. This was due to the Covid-19 pandemic which caused high prices of basic commodities and the loss of community jobs, so that the financial assistance provided by the government is barely sufficient to meet the needs of the poor. In addition, there is still a lack of program companions for the Family Hope Program, which only amounts to 4 people for 187 families. In the implementation of the Family Hope Program, the involvement of each implementing agency is often considered unimportant due to poor coordination of 3 (three) agencies, namely the Social Service, Sungai Kakap District Office, and the Village Government. The factors that influence the poor communication of the three aformentioned institutions are a fairly wide geographical area, assistants who do not have access to signals and village governments who do not understand the Operational Standards for work procedures.